2019
DOI: 10.1021/acschemneuro.9b00326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AV-1451 as a Weak, Nonselective Inhibitor of Monoamine Oxidase

Abstract: [18F]­AV-1451 is one of the most widely used radiotracers for positron emission tomography (PET) imaging of tau protein aggregates in neurodegenerative disorders. While the radiotracer binds with high affinity to tau neurofibrillary tangles, extensive clinical studies have simultaneously revealed off-target tracer accumulation in areas of low tau burden such as the basal ganglia and choroid plexus. Though there are a number of possible reasons for this accumulation, it is often attributed to off-target binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…There is increasing evidence that Flortaucipir also has a binding affinity to monoamine oxidases (MAO) isoforms confirmed by enzyme inhibition assays, autoradiography and in vivo PET (32)(33)(34). A recent in vitro study showed a comparable binding strength of Flortaucipir to tau fibrils and MAO (35).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Flortaucipir also has a binding affinity to monoamine oxidases (MAO) isoforms confirmed by enzyme inhibition assays, autoradiography and in vivo PET (32)(33)(34). A recent in vitro study showed a comparable binding strength of Flortaucipir to tau fibrils and MAO (35).…”
Section: Discussionmentioning
confidence: 99%
“…These data have generated considerable excitement for the utility of this signal, but they have illustrated shortcomings with regard to off-target binding. Notably, several of the first-generation ligands bind monoamine oxidase isoforms [28,77]. The substantial overlap in clinical presentation among primary tauopathies and other neurodegenerative syndromes further complicates the diagnostic utility of these agents.…”
Section: Strains In Diagnosis Of Tauopathiesmentioning
confidence: 99%
“…More selective PET radiotracers such as [ 18 F]THK5351 (Figure 1, 2 ) provided useful information on AD patients, but have recently been reported to have significant off‐target binding to monoamine oxidase (MAO B), reducing their potential use in AD diagnosis (Ng et al., 2017). Pyrrole derivatives such as [ 18 F]T807 (Figure 1, 3 ) also appear to show some off‐target MAO binding (e.g., Drake et al., 2019). Nevertheless, studies using [ 18 F]T807 and the related [ 18 F]RO6958948 (Figure 1, 4 ) continue for NFT imaging in AD (Honer et al., 2018).…”
Section: Introductionmentioning
confidence: 99%